Impact of geopolitical risks on resilience of lithium resource trade network: Based on complex network and panel regression analysis - ZHANG Yijun, BAI Wenbo, SONG Yi, CHEN Wu (Ziyuan Kexue)
[Objective] Lithium resources are regarded as the “lifeline” of the energy transition, yet their supply faces significant geopolitical risks. In this context, it is of great significance to clarify the impact of geopolitical risk on the resilience of the lithium resource trade network to ensure the security of lithium resource supply. [Methods] Based on trade data for lithium hydroxide and lithium carbonate from 22 countries (regions) from 2002 to 2022, this study explored the impact of geopolitical risks on the resilience of lithium resource trade network using a complex network method and a panel regression model. [Results] (1) During the sample period, the resilience of the lithium resource trade network showed a fluctuating upward trend, with a particularly significant increase after 2015. (2) Geopolitical risks had a significant negative impact on the resilience of lithium resource trade network, with the impact being more pronounced in core countries and regions of the network and in high-risk countries and regions. (3) Geopolitical risks negatively affected the resilience of lithium resource trade network by hindering trade cooperation and reducing foreign direct investment. [Conclusion] To mitigate the negative impact of geopolitical risks on lithium resource trade, it is necessary to establish a comprehensive early warning mechanism for emergency risks, promote the implementation of diversified import substitution strategies for lithium resources, and enhance the multi-layered global trade system. In addition, cooperation and risk management between major lithium-producing areas and neighboring countries (regions) should be strengthened.